2013
DOI: 10.1093/scan/nst052
|View full text |Cite
|
Sign up to set email alerts
|

Cry for her or cry with her: context-dependent dissociation of two modes of cinematic empathy reflected in network cohesion dynamics

Abstract: Two empathy-related processes were recently distinguished neuroscientifically: automatic embodied-simulation (ES) based on visceromotor representation of another's affective state via cingulo-insulary circuit, and emotional sharing relying on cognitive 'theory of mind' (ToM) via prefrontal-temporo-parietal circuit. Evidence that these regions are not only activated but also function as networks during empathic experience has yet to been shown. Employing a novel approach by analyzing fMRI fluctuations of networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
104
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 51 publications
1
104
0
1
Order By: Relevance
“…To compute the NCIs (Raz et al, 2014;Raz et al, 2012), the BOLD signal was first extracted for each node within each network (the dorsal salience, ventral salience, medial amygdala, ventrolateral amygdala, and dorsal amygdala networks) using a Gaussian mask with a 3-mm radius around the seed coordinates. Pearson correlations between the signals of all pairs of crossnetwork nodes were then computed in sliding 30-s (ten TRs) time windows.…”
Section: Network Cohesion Index Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…To compute the NCIs (Raz et al, 2014;Raz et al, 2012), the BOLD signal was first extracted for each node within each network (the dorsal salience, ventral salience, medial amygdala, ventrolateral amygdala, and dorsal amygdala networks) using a Gaussian mask with a 3-mm radius around the seed coordinates. Pearson correlations between the signals of all pairs of crossnetwork nodes were then computed in sliding 30-s (ten TRs) time windows.…”
Section: Network Cohesion Index Analysismentioning
confidence: 99%
“…The dorsal amygdala network was found to spatially overlap with both the ventral and dorsal salience networks, and therefore the cross-network NCIs for these networks were excluded from analysis. Before comparing the emotional rating and the NCIs, we excluded an interval whose duration was seven TRs (approximately the span of hemodynamic response) from the onset of each of the time series, to minimize the effect of novelty related to the change between the rest and movie conditions (Raz et al, 2014;Raz et al, 2012). The rating time series were preprocessed so that their length would fit the length of the NCI series.…”
Section: Network Cohesion Index Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…While resonating with the ideas illustrated above and suggesting that when interacting with another person the self is directly engaged via an emotional response to that other, this mechanism may occur also when merely observing an emotionally charged scene. We have demonstrated that a measure corresponding to the cohesiveness between emotional and embodied networks when viewing a sad movie correlated with a self reported measure of sadness towards that movie (Raz et al, 2014).…”
Section: A Theoretical Consideration Of the Effects Of Social Interacmentioning
confidence: 84%